(untitled) (Comprehensive Journal of Science, 2025)
This study aims to analyze the social phenomenon of seeking medical treatment abroad, focusing on its underlying motives and social impacts in the municipality of Al-Zawiya Al-Gharb. The research adopted a mixed methods approach, combining quantitative data collected through questionnaires from 200 patients with qualitative insights from in-depth interviews involving 30 participants, including patients and healthcare providers. The findings indicate that the motives behind seeking treatment abroad stem from both structural factors (limited healthcare capacities at 78%, bureaucratic obstacles at 65%) and subjective factors (loss of trust at 72%, pursuit of social prestige at 55%). The study also reveals profound social and economic consequences, such as the depletion of household resources, the deepening of social inequalities, and the erosion of trust in public institutions. It concludes by emphasizing the need for comprehensive policies that strengthen the local healthcare system and address the negative social attitudes contributing to this phenomenon.